2021
DOI: 10.47602/johah.v1i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Validation and utility of the Meaning in Life Measure for Turkish university students

Abstract: The Meaning in Life Measure (MILM) is a new measure for assessing meaning in life by addressing problems associated with existing measures of meaning in life (absence of items related to reflectivity, felt sense, and mattering). For the first time, this study aimed to test the psychometric properties of the MILM for university students in Turkey. We used a sample of 376 university students (Mage=24.03±4.65 years) who participated in an online survey including the MILM, the Adult Dispositional Hope Scale, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…We recommend the following topics for advancing personal growth among university students: developing proactivity and career adaptability, becoming a better version of oneself, discovering the winning track, developing a positive mindset for greater inner strength, fostering greater self-knowledge, enhancing happiness based on positive thought, furthering the X-Factor, finding meaning in life, cultivating hope and optimism, nurturing PERMA-oriented well-being, and mastering the art-of-living (cf. Green, 2020b , 2021a , 2021b , 2021c , 2021d ; Green et al, 2015a , 2015b , 2015c , 2015d , 2020b , 2021a , 2022 ; Lang & Schmitz, 2016 ; Yıldırım et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recommend the following topics for advancing personal growth among university students: developing proactivity and career adaptability, becoming a better version of oneself, discovering the winning track, developing a positive mindset for greater inner strength, fostering greater self-knowledge, enhancing happiness based on positive thought, furthering the X-Factor, finding meaning in life, cultivating hope and optimism, nurturing PERMA-oriented well-being, and mastering the art-of-living (cf. Green, 2020b , 2021a , 2021b , 2021c , 2021d ; Green et al, 2015a , 2015b , 2015c , 2015d , 2020b , 2021a , 2022 ; Lang & Schmitz, 2016 ; Yıldırım et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…PMT is applicable here because for the threat of the pandemic, there is an effective recommended response in the form of well-recognized COVID-19 preventive strategies that can be practiced by individuals ( Floyd et al 2000 ). The fear of COVID-19 may therefore be a motivator for practicing COVID-19 preventive behaviors ( Yıldırım, Geçer, & Akgül, 2021 ). Second, this research underscores the importance of COVID-19 preventive behaviors in nurturing greater satisfaction with life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of such innovative studies' results can be compared to quantitative results to get a more valid picture of what is happening with the college students. Additionally, more studies focusing on meaning among college students are needed (Tanhan, 2019(Tanhan, , 2020Yıldırım et al, 2021).…”
Section: Implications For Researchmentioning
confidence: 99%
“…Researchers across globe experience biopsychosocial, spiritual, and economic issues (Otanga et al, 2021;Tanhan & Francisco, 2019;Tanhan & Strack, 2020). Similarly, many researchers found that College students in Turkey also experience many biopsychosocial, spiritual, and economic issues (Bayın et al, 2021;Demir et al, 2021;Doyumğaç et al, 2021;Tanhan, 2020;Yıldırım et al, 2021). All these researchers called for effective research.…”
mentioning
confidence: 99%